Permintaan Mahar Perkawinan Dan Stigmatisasi Negatif Terhadap Perempuan - Zulaikha, Siti (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2020)
A dowry in marriage is something that is given at the request of the woman, although bargaining about the amount is common and common, until an agreement is reached between the two prospective brides. Although statistically 'there is no provision regarding the amount of dowry, there is also no limit to the smallest size of the dowry. This becomes interesting when the size of the dowry is then questioned. The fact in society is that for women who determine a dowry not in a large amount, then the woman will be considered good, on the other hand women will be underestimated if they are judged to determine their dowry in a large amount. What should be seen is the substance of the dowry, apart from being a form of respect and exaltation, the dowry must begin to be seen as a long-term investment, meaning that if it is needed later, with the wife's permission, the dowry can be used together in accordance with the provisions of syara'.